Population Management of Diabetes in a High-Need Urban Community in the Bronx: The Experience of Montefiore Medical Center. (July 2013) - Farrell, Patricia; Barnaby, Sandra; Galarza, Tahnee; Simonson, Julie K.; Zonszein, Joel; Meara, Anne; Chung, Henry; Figueira, Rhonda; Felleman, Sheila
Purpose: The purpose of this study is to examine the impact of a Care Management Organization (CMO) Diabetes Disease Management Program (DDMP) in improving diabetes outcomes among high-risk patients with type 2 diabetes (T2DM) in the Bronx, New York. Methods: An interventional, nonrandomized study design was used to assess the effectiveness of the DDMP. Patients older than 18 years who had T2DM and an A1C persistently 8% or greater or with a cardiovascular comorbidity were characterized as high risk and received intensive disease management. Patients served as their own controls, with data collection and analysis occurring 12 months prior to and 12 months after enrollment in DDMP. Data collection included screening rates for A1C, low-density lipoprotein (LDL) cholesterol, depression, smoking status, and annual influenza vaccine administration. Changes in A1C and LDL cholesterol were also analyzed. Statistical analyses were conducted using Minitab. McNemar's chi-square and paired t tests were used to assess within-group changes from baseline to final outcomes. Results: Significant improvements in screening rates for A1C, LDL, depression, smoking status, and annual influenza vaccine administration were found among high-risk/intensively managed patients in the DDMP. Improvements in clinical measures were also achieved in this group. Provider and patient satisfaction surveys were positive, with 92% of patients believing that the program helped them better understand their disease. Conclusions: A DDMP among high-risk patients has shown promise in improving the quality of care for patients with diabetes. This program has relevance for other integrated delivery systems that are developing accountable care approaches.